Improving CO2 Separation Performance of MIL‐53(Al) by Incorporating 1‐n‐Butyl‐3‐Methylimidazolium Methyl Sulfate. Issue 7 (9th May 2019) - Kulak, Harun; Polat, H. Mert; Kavak, Safiyye; Keskin, Seda; Uzun, Alper
Abstract : 1‐ n ‐Butyl‐3‐methylimidazolium methyl sulfate is incorporated into MIL‐53(Al). Detailed characterization is done by X‐ray fluorescence, Brunauer–Emmett–Teller surface area, scanning electron microscopy, X‐ray diffraction, Fourier‐transform infrared spectroscopy, and thermogravimetric analysis. Results show that ionic liquid (IL) interacts directly with the framework, significantly modifying the electronic environment of MIL‐53(Al). Based on the volumetric gas adsorption measurements, CO2, CH4, and N2 adsorption capacities decreased from 112.0, 46.4, and 19.6 cc (STP) gMIL‐53(Al) −1 to 42.2, 13.0, and 4.3 cc (STP) gMIL‐53(Al) −1 at 5 bar, respectively, upon IL incorporation. Data show that this postsynthesis modification leads to more than two and threefold increase in the ideal selectivity for CO2 over CH4 and N2 separations, respectively, as compared with pristine MIL‐53(Al). The isosteric heat of adsorption (Qst) values show that IL incorporation increases CO2 affinity and decreases CH4 and N2 affinities. Cycling adsorption–desorption measurements show that the composite could be regenerated with almost no decrease in the CO2 adsorption capacity for six cycles and confirm the lack of any significant IL leaching. The results offer MIL‐53(Al) as an excellent platform for the development of a new class of IL/MOF composites with exceptional performance for CO2 separation. Abstract : 1‐ n ‐Butyl‐3‐methylimidazolium methyl sulfate was incorporated into MIL‐53(Al). Characterization indicated direct interactions between ionic liquid (IL) and MIL‐53(Al). Adsorption isotherms of CH4, CO2, and N2 on the parent and IL‐incorporated MIL‐53(Al) were measured up to 5 bar. CO2 selectivity over N2 was enhanced by more than three‐times upon the incorporation of IL into MIL‐53(Al). IL incorporation also doubles CO2 /CH4 selectivity of MIL‐53(Al).